Technology and organization essays in honour of Joan Woodward - Phillips, Nelson.; Griffiths, Dorothy S.; Sewell, Graham. (Research in the sociology of organizations ;, 2010)
It is now 35 years since the death of Professor Joan Woodward, one of the founding figures of organization studies. Professor Woodward died in 1971 at the age of 54 after a relatively brief but highly distinguished career as a management researcher and teacher, and just six years after the publication of her landmark book Industrial Organization. At the time of her death, Professor Woodward was the Chair in Industrial Sociology at Imperial College London, having been elected as only the second women professor at the College in 1970. She joined the Production Engineering and Management Section of Imperial in 1958 and the majority of her most important work was published during this period. Prior to this she had spent a number of years at the South East Essex College of Technology where she conducted much of the empirical work that informed her significant contributions to the field.